Changes in Gastric Smooth Muscle Cell Contraction during Pregnancy: Effect of Estrogen - Othman A. Al-Shboul; Hanan J. Al-Rshoud; Ahmed N. Al-Dwairi; Mohammad A. Alqudah; Mahmoud A. Alfaqih; Ayman G. Mustafa; Mohammad Jaafar (Journal of Pregnancy)
It is well known that pregnancy is associated with frequent gastrointestinal (GI) disorders and symptoms. Moreover, previous reports have shown that estrogen, which changes in levels during pregnancy, participates in the regulation of GI motility and is involved in the pathogenesis of various functional disorders in the stomach. The aim of the current study was to explore the changes in the expression of estrogen receptors (ERs) and examine the effect of estrogen on nitric oxide- (NO-) cyclic guanosine monophosphate (cGMP) pathway and thus relaxation in gastric smooth muscle cells (GSMC) during pregnancy. Single GSMC from early-pregnant and late-pregnant Sprague-Dawley rats were used. Protein and mRNA expression levels of ERs were measured via specifically designed enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR), respectively. NO and cGMP levels were measured via specifically designed ELISA kits. Effect of estrogen on acetylcholine- (ACh-) induced contraction of single GSMC was measured via scanning micrometry in the presence or absence of the NO synthase inhibitor, N-nitro-L-arginine (L-NNA), or guanylyl cyclase inhibitor, 1H-[1,2,4]oxadiazolo[4,3,-a]quinoxalin-1-one (ODQ). Estrogen increased both NO and cGMP levels and their levels were greater in early compared to late pregnancy. Expression of ERs was greater in early compared to late pregnancy. ACh induced greater contraction of GSMC in late pregnancy compared to early pregnancy. Estrogen inhibited ACh-induced contraction in both periods of pregnancy. Importantly, pretreatment of GSMC with either L-NNA or ODQ abolished estrogen inhibitory action on muscle contraction. In conclusion, GSMC contractile behavior undergoes drastic changes in response to estrogen during pregnancy and this might explain some of the pregnancy-associated gastric disorders.